Moulded calculus of common bile duct mimicking a stenosis - Jamry, Andrzej; Brocki, Marian; Śmigielski, Jacek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Bile duct stenosis, in most cases, appears to be the consequence of pancreatic head, ampulla of Vater and bile duct tumours, cholangitis sclerosans, as well as iatrogenic damages, which may all be diagnosed during endoscopic retrograde cholangiopancreatography (ERCP). In very rare cases the restriction may result from an atypically shaped wedged stone. This situation creates many diagnostic problems, which in the majority of cases can be solved using imaging studies. However, in some patients even a significant extension of diagnostic procedures may not lead to a correct diagnosis. We present a diagnostically difficult case of a deposit imitating restriction. We present a 70-year-old woman with common bile duct restriction undiagnosed despite several ultrasound examinations (USG), computed tomography (CT), double magnetic resonance cholangiopancreatography (MRCP) and endoscopic retrograde cholangiopancreatography (ERCP). Only after the third ERCP examination a fragmented, by formerly introduced prosthesis, deposit, imitating narrowing, was revealed. Identification of bile duct deposits depends on their composition, localisation and the imaging techniques used. Pigment calculi with atypical shape, bile density, air density or surrounding tissue density are very difficult to diagnose. Thus, the sensitivity of common bile duct stone detection in USG, CT, MRCP and endoscopic ultrasound (EUS) is 5–88%; 6–88%; 73–97%; and 84–98%, respectively. Moreover, ERCP may not diagnose the character of the restriction even in 5.2% up to 30% of the patients. Consequently, assessment of diagnosis in a number of patients is difficult. A deposit imitating common bile duct (CBD) restriction is a rare, difficult to diagnose phenomenon, which should be taken into account during differential diagnosis of CBD restrictions.